Perjalanan Prestasi Atlit Wushu Sanda Jawa Tengah Di Asian Game 2018 (Universitas Negeri Semarang, 2023)
The purpose of this study was to describe and conclude the development of the achievements of the wushu sanda athletes in champions. This research is a descriptive study with data collection techniques through observation and documentation. Analyze data through life experiences. The sample in this study were the athletes of the Central Java sanda wushu. The results of this study indicate that the development component at the regional level in this case in Central Java, as well as at the national level, tends to be good, because at the regional level it has carried out long-term coaching from junior to senior. For infrastructure, it is also sufficient, maybe only more to improve when the update is faster, because the equipment used only lasts a few months. And for vitamins, supplements and try out are still lacking. Meanwhile, at the national level, the development is good because all infrastructure, supplements and vitamins have also been fulfilled. The conclusion of the research is that the guidance at the regional level in this case in Central Java, as well as at the national level, tends to be good although there are still some shortcomings.